Sound Fields in Complex Listening Environments - Vorländer, Michael (SAGE Publications, 2011)
The conditions of sound fields used in research, especially testing and fitting of hearing aids, are usually simplified or reduced to fundamental physical fields, such as the free or the diffuse sound field. The concepts of such ideal conditions are easily introduced in theoretical and experimental investigations and in models for directional microphones, for example. When it comes to real-world application of hearing aids, however, the field conditions are more complex with regard to specific stationary and transient properties in room transfer functions and the corresponding impulse responses and binaural parameters. Sound fields can be categorized in outdoor rural and urban and indoor environments. Furthermore, sound fields in closed spaces of various sizes and shapes and in situations of transport in vehicles, trains, and aircrafts are compared with regard to the binaural signals. In laboratory tests, sources of uncertainties are individual differences in binaural cues and too less controlled sound field conditions. Furthermore, laboratory sound fields do not cover the variety of complex sound environments. Spatial audio formats such as higher-order ambisonics are candidates for sound field references not only in room acoustics and audio engineering but also in audiology.